PERTANGGUNGJAWABAN NOTARIS DALAM MELAKSANAKAN TUGASNYA SEBAGAI PEJABAT PUBLIK TERHADAP AKTA YANG DITERBITKAN MENIMBULKAN PERKARA PIDANA (Studi Putusan Mahkamah Agung No. 1014 K/PID/2013) - PARULIAN H SITOMPUL (PREMISE LAW JURNAL, 2016)
In reality, a Notary, in performing his duty, is not usually guided by UUJN (Notarial Act) as what has occurred in the Ruling of the Supreme Court No. 1014 K/PID/2013 in which Ninoek Poernomo, the Notary, is charged with criminal act, that is, falsifying a deed. Public prosecutor prosecuted the defendant 1 (one) year imprisonment. The research used judicial normative method. The gathered data were analyzed by using qualitative data analysis. The result of the research showed that the defendant had violated UUJN and Notarial Code of Ethics and was consciously violated Article 264 of the Penal Code so that he was responsible for what he had done. Concerning the deed, it is not automatically cancelled but it becomes an underhanded deed; it can only be cancelled by judge’s verdict through civil complaint. Some factors which cause a Notary to be involved in a criminal act are notarial ethics and taking the side of one of the parties, the truth of the data filed by the parties concerned to a Notary, supervision on a Notary, and incorrect rules. Keywords : Notary, Public Official